Innovative way of development of the internal audit of the enterprise (Journal of Economic Research & Business Administration, 2016)
Currently set by the President of the Republic of Kazakhstan Nursultan Nazarbayev task «Nurly zhol- the way in The Future" in the message about entry of the country among the 30most developed countries requires a large number of transformations of many economic relations. Among these transformations preference is given to intensive ones e.t. the use of more efficient production methods. In this regard, innovative way of development is the most appropriate, as the primary method, firstly, to overcome the economic crisis; secondly, to ensure stable long-term economic growth. Nowadays, the problem of managing innovation factor as incentive mechanism of development through improved systems of accounting, audit and control by their adaptation to the requirements of today is becoming more and more actual.
Keywords: internal audit; inspection; management accounting; analysis.